2022
DOI: 10.3389/fnagi.2022.1002642
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state functional connectivity alteration in elderly patients with knee osteoarthritis and declined cognition: An observational study

Abstract: ObjectiveThis study is designed to investigate the brain function changed regions in elderly patients with knee osteoarthritis (KOA) and to explore the relationship between neuropsychological tests and resting-state functional magnetic resonance imaging (rs-fMRI) network to clarify the possible mechanism underlying cognitive changes in KOA patients.Materials and methodsFifty-two patients aged ≥ 65 with KOA and twenty-two healthy-matched controls were recruited in this study. All participants were given rs-fMRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
(46 reference statements)
0
3
1
Order By: Relevance
“…Knee osteoarthritis (KOA) is a common disabling disease in adults worldwide, resulting in functional limitations, disability, and signi cant healthcare costs. Recent advances in neurophysiology provided new insights into the relationship between KOA and cognitive function, suggesting a decline in cognitive function in patients with KOA, particularly in the elderly (Lin et al, 2022). Memory impairment is the most typical and common type of cognitive decline in older adults (Zahodne et al, 2015), but evidence on the dimension of memory decline in KOA patients has been lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knee osteoarthritis (KOA) is a common disabling disease in adults worldwide, resulting in functional limitations, disability, and signi cant healthcare costs. Recent advances in neurophysiology provided new insights into the relationship between KOA and cognitive function, suggesting a decline in cognitive function in patients with KOA, particularly in the elderly (Lin et al, 2022). Memory impairment is the most typical and common type of cognitive decline in older adults (Zahodne et al, 2015), but evidence on the dimension of memory decline in KOA patients has been lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging research has shown that the presence of brain imaging changes in patients with KOA is associated with cognitive decline (Lin et al, 2022). Previous studies suggested that cognitive function in patients with KOA may be related to the brain regions structural change (Tanner et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We didn't nd signi cant abnormalities as for the global topological properties including the small-world and network e ciency in patients with KOA when compared with healthy controls. In previous studies, decreased local e ciency and small worldness have been suggested in elderly KOA patients (age ≥ 65) as compared to healthy controls (Lin et al, 2022). However, in our cohort, the KOA participant are relatively younger (mean age: 55.1± 8.9 years).…”
Section: Discussioncontrasting
confidence: 50%
“…Previous studies have suggested altered temporal-frontal (dorsolateral superior frontal, middle frontal, and left medial superior frontal gyrus) rsFC in patients with end-stage KOA (Kang et al, 2022). Lower functional connectivity of the temporal cortex has been suggested in KOA (Lin et al, 2022). Exercise can decrease the rsFC of the parietal, temporal and occipital cortices in KOA (Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 94%